Pendampingan Pengembangan Tempat Wisata Baru Berbasis Masyarakat di Panbo Beach Kabupaten Kampar - Helly Aroza Siregar; M. Hasmil Adiya; Suroyo (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
Community-based tourism is an effective step to empower local communities in managing tourist attractions. Panbo beach is a new tourist spot in the Kampar Regency area whose management is still very limited. The main problems faced are the number of visitors who are still minimal and financial management is very simple. This community service activity aims to create a website for Panbo Beach so that this tourist spot can be marketed online. After the website is created, then training is held for the use of the website. Another activity is conducting training in the preparation of financial reports. The results achieved in the implementation of service are the ability of participants to operate the website and the understanding of financial reports of the participants increased.